2007
DOI: 10.1136/adc.2006.104596
|View full text |Cite
|
Sign up to set email alerts
|

Conservative treatment for patent ductus arteriosus in the preterm

Abstract: Background: A patent ductus arteriosus (PDA) is common among preterms, and prophylactic medical treatment has been advocated as the first-line approach. Conservative treatment may result in similar outcome, but without exposure to the harmful side effects of medication. A retrospective analysis revealed a ductal closure rate of 94% after conservative treatment with adjustment of ventilation (lowering the inspiratory time and increasing positive end expiratory pressure) and fluid restriction. Objective: To stud… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
80
1
6

Year Published

2009
2009
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 115 publications
(87 citation statements)
references
References 29 publications
0
80
1
6
Order By: Relevance
“…The rate of ligation in the present study, in infants receiving more than one course of indomethacin, although higher than reported in recent cohort studies (6,8,(10)(11)(12), was still within the range reported in the literature (4,5,15,17,18). Koehne et al (4) reported an overall ligation rate of 57% and a 34% ligation rate in 101 babies who had indomethacin treatment.…”
Section: Discussioncontrasting
confidence: 51%
“…The rate of ligation in the present study, in infants receiving more than one course of indomethacin, although higher than reported in recent cohort studies (6,8,(10)(11)(12), was still within the range reported in the literature (4,5,15,17,18). Koehne et al (4) reported an overall ligation rate of 57% and a 34% ligation rate in 101 babies who had indomethacin treatment.…”
Section: Discussioncontrasting
confidence: 51%
“…Strategies avoiding use of indomethacin or ibuprofen yield outcomes comparable to contemporaneous external benchmarks. 51,52 Less frequent use of surgical ligation in infants with PDA after failure of indomethacin prophylaxis was associated with a lower rate of necrotizing enterocolitis and no increase in rates of other adverse outcomes. 53 Reduced use of indomethacin and ligation at 1 center was associated with an increased rate of the combined outcome of death or chronic lung disease but no increase in rates of individual morbidities or mortality.…”
Section: Evidence For Benefits Of Treatmentmentioning
confidence: 99%
“…Because of the paucity of published trials documenting outcomes in neonatal intensive care units (NICUs) where PDAs were not treated reflexively with cyclo-oxygenase inhibitors or LIGATE, [5][6][7] we adopted PDA management guidelines in 2008 that emphasized watchful waiting for spontaneous closure, modest fluid restriction and limited use of indomethacin (INDO) and LIGATE to only those infants who met certain cardiorespiratory distress criteria. The purpose of this manuscript is to describe our beforeafter observational study to determine whether our new PDA management guidelines were associated with improved, worsened or unusual NICU outcomes.…”
Section: Introductionmentioning
confidence: 99%